Czy klasyczna biografia pisarza może ładnie się zestarzeć? Marietta Czudakowa o Michaile Bułhakowie - Korcz, Karolina (Zagadnienia Rodzajów Literackich, 2021)
The article addresses the issue of generic and cognitive attractiveness of a monograph based on the work of Marietta Chudakova entitled, Mikhail Bulgakov: The Life and Times, which was published with a more than thirty years delay. The main purpose of the sketch is the reflection on the biography author’s research project, the methodology, the connection between the research sources and the writing strategy to which the structure of this article is devoted. The introduction of the article describes how the author realized the proposed honesty and authenticity while adopting a certain research method that is perceived ethically. The next part of the article focuses on the implemented methods which are mainly used in the fields of history and literary studies while using certain sources such as archives and witness accounts that are not accessible for modern researchers. The last part of the article concentrates on the influence of “me” as an author on the way the narrative of the biography is conducted. The analysis of the given problems allowed the results of a particular research work to be seen. It also showed how a documental biography may be still attractive to a reader despite the changes in reception.